2010
DOI: 10.1093/jnci/djq101
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarker Expression and Risk of Subsequent Tumors After Initial Ductal Carcinoma In Situ Diagnosis

Abstract: Biomarkers can identify which women who were initially diagnosed with DCIS are at high or low risk of subsequent invasive cancer, whereas histopathology information cannot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
268
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(298 citation statements)
references
References 43 publications
18
268
3
4
Order By: Relevance
“…9,10,24,28 Additionally, Kepple et al 29 and Kerlikowske et al 30 found Her-2 positivity to be significantly associated with an increased risk of recurrence in DCIS. This correlates with findings in the previous study, in which Her-2 status was inversely related to bcl-2 status, a marker of low-grade breast neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,24,28 Additionally, Kepple et al 29 and Kerlikowske et al 30 found Her-2 positivity to be significantly associated with an increased risk of recurrence in DCIS. This correlates with findings in the previous study, in which Her-2 status was inversely related to bcl-2 status, a marker of low-grade breast neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Kerlikowske et al (2010) have recently described an association between p16 Ink4a overexpression in breast ductal carcinoma in situ and the risk of subsequent DCIS or invasive cancer. In brief, p16 Ink4a overexpression together with a high ki67 and COX-2 overexpression was associated with progression to an invasive carcinoma, whereas p16 Ink4a overexpression with high ki67 but without COX-2 overexpression was associated with subsequent DCIS.…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%
“…This distinction has a critical impact on patient prognosis: whereas women with DCIS show no reduction in survival 5 y after diagnosis, those with invasive cancers have a 15-74% reduction in 5-y survival rates depending on the extent of tumor invasion at diagnosis (2). Given these observations, there is significant interest in finding genes that promote the invasive progression of early-stage tumors (3). Previous studies have sought molecular alterations present in invasive tumors but not DCIS, leading to the identification of hundreds of genomic and gene-expression alterations specifically associated with invasive cancers (4)(5)(6).…”
mentioning
confidence: 99%